PRAKTIK BIDAN DALAM PENGGUNAAN ALGORITMA MANAJEMEN TERPADU BAYI MUDA PADA KUNJUNGAN NEONATAL - Iraningsih, Wahyu; Azinar, Muhammad (Unnes Journal of Public Health, 2017)
Neonatal mortality in Indonesia declined slowly and tended to stagnant in number of 20/1000 live births. Proportion of neonatal mortality in Cilacap Regency at 2015 reached 69% of infant mortality. A quality neonatal care might decrease 34-62% mortality, but not all midwives used integrated management of neonatal and childhood illness (IMNCI) algorithm. This study aimed to figure out factors associated with midwives’ practice on using IMNCI algorithm in neonatal care. This study used cross sectional approach with purposive sampling until 60 respondents were collected. Data were analyzed with chi-square test. There were association between knowledge (p=0.000), attitude (p=0.023), availability of facilities (p=0.023), support from leader (p=0.017), length of work (p=0.011), and supervision (p=0.039) with midwives’ practice on using IMNCI algorithm. There were not assocation on age (p=0.124), employment status (p=0.124), extra work load (p=0.290), and reward (p=0.053). Factors associated with midwives’ practice on using IMNCI algorithm in neonatal care were knowledge, attitude, availability of facilities, support from leader, length of work, and supervision.